An Analysis of Affective Factors of Deaf college Students' English Learning Based on Affective Filtering Hypothesis - LIU, GAI (Pacific International Journal, 2022)
The College English course for deaf students is a compulsory course for students during the university period. The influence of learning motivation, learning anxiety and self-confidence on deaf students' English learning should also be considered. By balancing various emotional factors, students can obtain better learning results. The influence of affective factors on learning is undeniable. Therefore, in view of these major affective factors, combined with the learning reality of deaf students and the observation of front-line teachers and front-line classrooms in the investigation, the author explores the influence of several affective factors on deaf students' English learning, and puts forward improvement measures and suggestions.